Next-Generation Actuators Leading Breakthroughs - Higuchi, Toshiro; Suzumori, Koichi; Tadokoro, Satoshi (Springer London : Imprint: Springer, 2010)
Actuators, which move and manipulate objects, are the key technological components for all modern science and technologies. The advent of new, outstanding actuators will bring innovation to a range of different areas - such as basic science, industry, medicine, welfare, and the global environment - and in this way will provide us with a better quality of life. Next-Generation Actuators Leading Breakthroughs is the proceedings of the final symposium of MEXT Grant-in-Aid for Scientific Research on Priority Areas: Next-Generation Actuators Leading Breakthroughs, held in January 2010. This project pursues the realization of next-generation actuators and accumulates the common basic technologies for actuators, with a view to possible future applications. Since the realization of next-generation actuators requires an interdisciplinary approach, the research has been organized according to a broad technological perspective that consists of: • actuators for small motion of nano-meters; • small-size actuators of micro-meters structures; • intelligent actuators for functional motions; • power actuators for large force/torque; and • actuators for special environments. Next-Generation Actuators Leading Breakthroughs also deals with common fundamental technologies for these actuators, such as intelligent materials, machining processes, control technologies, evaluation methods, and system integration. It provides cutting-edge research for researchers, postgraduates, and practitioners in mechanical, electrical, and materials industries.